ED151, A Flawed Approach - Brian Andrew (Australasian Accounting, Business and Finance Journal, 2007)
This paper argues the recent proposals expressed by the Australian Accounting StandardBoard in Exposure Draft 151 contradicts the historical trend of standard setters attemptingto achieve the objective of financial reporting, that is, the provision of decision-usefulinformation for users of general purpose financial reports. Historically, standard settershave tried to achieve this objective by reducing alternative treatments in accountingstandards and providing increasing levels of information for users. Exposure Draft 151affects many standards, however, this paper focuses on the proposal to allow preparers theoption of selecting between the direct or indirect method of presenting cash flows fromoperations in the statement of cash flows. We argue that this discretion contradicts thestated objective of financial reporting, as stated in the Conceptual Framework, as it will leadto the widespread adoption of the less informative indirect method, due to a structural biasin the requirements of AASB 107 and IASB 7, the relevant standards relating to thestatement of cash flows.